Case Report: Novel truncating PPM1D variant in a dichorionic diamniotic (DCDA) twin with Jansen-de Vries syndrome. an updated perspective - Merida De la Torre, Francisco Javier; Porta Pelayo, Javier; Ortiz-Martín, Inmaculada (Frontiers in Genetics, 2025)
IntroductionJansen-de Vries syndrome (JDVS) is a rare autosomal dominant neurodevelopmental disorder caused by truncating variants in exons 5 and 6 of the PPM1D gene. Its diagnosis is often delayed due to symptom overlap with more common conditions such as autism spectrum disorder (ASD) and attention-deficit/hyperactivity disorder (ADHD). This case report highlights the unique presentation of JDVS in one of a pair of dichorionic diamniotic (DCDA) twin brothers, both with ASD/ADHD, underscoring the diagnostic value of genetic testing.Case presentationA 6-year-old boy presented with delayed language development, learning difficulties, behavioral issues, restrictive eating, and impaired autonomy. His twin brother, although also diagnosed with ASD/ADHD, exhibited milder symptoms. Trio-whole-exome sequencing revealed a de novo frameshift mutation (c.1411_1412del) in PPM1D in the proband, classified as pathogenic. The brother had no such variant.Interventions and outcomesThe proband received multidisciplinary interventions including behavioral therapy and speech support. Follow-up showed improvements in language, sleep, and academic performance, though behavioral and sphincter issues persist. The twin without the mutation was discharged from mental health services, while his brother remains under annual review.ConclusionThis case emphasizes the expanding phenotypic spectrum of JDVS and illustrates the diagnostic value of trio-WES in neurodevelopmental disorders with overlapping features. It also highlights the potential for discordant phenotypic expression in twins and the need for individualized diagnostic assessment.